Nonparametric Estimates of the Labor-Supply Effects of Negative Income Tax Programs - Ashenfelter, Orley; Plant, Mark W. (Journal of Labor Economics, 1990)
This article reports nonparametric estimates of the effect of labor-supply behavior on the payments to families enrolled in the Seattle/Denver Income Maintenance Experiment. The randomized assignment of families to the treatment groups in this experiment was designed to permit the calculation of these nonparametric estimates. However, the nonparametric estimates have never been reported, even though they are easy to construct using a simple weighting procedure. Unfortunately, responses to the data collection instrument (which depended on costly surveys) were not random, and this opens up some ambiguity in the results.